The Interrelation Poverty-Unemployment from the Theory of Entropy in Modern Societies - Nieto-Chaupis, Huber (2021)
In this paper, a mathematical model based on uncertainties to describe the potential interrelation between unemployment and poverty by using the Shannon’s entropy is presented. Essentially, when social systems that are characterized by having a large number of variables and interact among them, one can expect a kind of disorder affecting the main functionalities would have to be exhibited by any modern society. Thus, Shannon’s entropy fits well the social phenomenology as to describe through uncertainties these interrelations. Moreover, it was added to this debate the idea that geographical divisions might also to be relevant as to understand the transition from unemployment to poverty. Finally, the theoretical results are discussed.